Immature human dendritic cells enhance their migration through KCa3.1 channel activation. Issue 4 (April 2016) - Crottès, David; Félix, Romain; Meley, Daniel; Chadet, Stéphanie; Herr, Florence; Audiger, Cindy; Soriani, Olivier; Vandier, Christophe; Roger, Sébastien; Angoulvant, Denis; Velge-Roussel, Florence
Graphical abstract: Highlights: Human dendritic cell migration needs sustained Ca 2+ entry managed by KCa3.1. The CCR expressions were also controlled by KCa3.1. KCa3.1 masters human immature dendritic cell migration. Abstract: Migration capacity is essential for dendritic cells (DCs) to present antigen to T cells for the induction of immune response. The DC migration is supposed to be a calcium-dependent process, while not fully understood. Here, we report a role of the KCa3.1/IK1/SK4 channels in the migration capacity of both immature (iDC) and mature (mDC) human CD14 + -derived DCs. KCa3.1 channels were shown to control the membrane potential of human DC and the Ca 2+ entry, which is directly related to migration capacities. The expression of migration marker such as CCR5 and CCR7 was modified in both types of DCs by TRAM-34 (100 nM). But, only the migration of iDC was decreased by use of both TRAM-34 and KCa3.1 siRNA. Confocal analyses showed a close localization of CCR5 with KCa3.1 in the steady state of iDC. Finally, the implication of KCa3.1 seems to be limited to the migration capacities as T cell activation of DCs appeared unchanged. Altogether, these results demonstrated that KCa3.1 channels have a pro-migratory effect on iDC migration. Our findings suggest that KCa3.1 in human iDC play a major role in their migration and constitute an attractive target for the cell therapy optimization.